2010
DOI: 10.1016/j.learninstruc.2009.02.019
|View full text |Cite
|
Sign up to set email alerts
|

In the eyes of the beholder: How experts and novices interpret dynamic stimuli

Abstract: Jarodzka, H., Scheiter, K., Gerjets, P., & Van Gog, T. (2010). In the eyes of the beholder: How experts and novices interpret dynamic stimuli. Learning and Instruction, 20, 146-154. doi:10.1016/j.learninstruc.2009.02.019Tasks with a complex, dynamic visual component require not only the acquisition of conceptual/procedural but also of perceptual/attentional skills. This study examined expertise differences in perceiving and interpreting complex, dynamic visual stimuli on a performance and on a process level, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
190
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(209 citation statements)
references
References 27 publications
13
190
1
5
Order By: Relevance
“…The second approach involves a two-step expert modeling procedure similar to Jarodzka et al's eye movement modeling examples known as EMMEs (see Jarodzka et al 2010;Van Gog et al 2009). In this approach, first expert argumentation schemas are collected, here with respect to the argumentation used in a specific case.…”
Section: Determining the Learner's Internal Argumentative Scriptmentioning
confidence: 99%
“…The second approach involves a two-step expert modeling procedure similar to Jarodzka et al's eye movement modeling examples known as EMMEs (see Jarodzka et al 2010;Van Gog et al 2009). In this approach, first expert argumentation schemas are collected, here with respect to the argumentation used in a specific case.…”
Section: Determining the Learner's Internal Argumentative Scriptmentioning
confidence: 99%
“…These studies showed that experts possess sophisticated visual observation skills which enable them to visually search relevant features of a stimulus within irrelevant features and to interpret these observations correctly (e.g., Antes and Kristjanson 1991;Charness et al 2001;Jarodzka et al 2010a; Underwood et al 2003). Novices, however, get easily distracted by salient, but potentially irrelevant, elements of a visual stimulus, whilst missing relevant information (Jarodzka et al 2010a;Lowe 1999). …”
Section: Role Of Visual Observations In Clinical Reasoningmentioning
confidence: 99%
“…Although no studies have yet investigated which differences in visual observation skills exist between experts and novices when processing dynamic stimuli in the medical domain such as patient video cases, expertise differences in visual observation skills have been shown for dynamic, realistic stimuli in other domains, such as biological classification of motion patterns (Jarodzka et al 2010a) or car driving (Underwood et al 2003).…”
Section: Role Of Visual Observations In Clinical Reasoningmentioning
confidence: 99%
“…An alternative approach situated in the context of fish locomotion can be seen in Jarodzka, Scheiter, Gerjets, and van Gog (2010). Balslev et al (2012) used think-aloud in the context of viewing films depicting infants with seizures and conditions resembling seizures.…”
Section: Critical Examination Of Studies Combining Eye Tracking and Vmentioning
confidence: 99%